1998
DOI: 10.1086/301888
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Route for Multistep Tumorigenesis in a Novel Case of Hereditary Renal Cell Cancer and a t(2;3)(q35;q21) Chromosome Translocation

Abstract: Through allele-segregation and loss-of-heterozygosity analyses, we demonstrated loss of the translocation-derivative chromosome 3 in five independent renal cell tumors of the clear-cell type, obtained from three members of a family in which a constitutional t(2;3)(q35;q21) was encountered. In addition, analysis of the von Hippel-Lindau gene, VHL, revealed distinct insertion, deletion, and substitution mutations in four of the five tumors tested. On the basis of these results, we conclude that, in this familial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 34 publications
(45 reference statements)
6
47
0
Order By: Relevance
“…In two living brothers of this family who were diagnosed with renal cell cancers, a t(2;3)(q33;q21) constitutional translocation was found, but it is probable, because of the clinical features of the other five RCC cases that developed in close relatives, that the relatives were also carriers of this chromosomal abnormality. Another family segregating t(2;3)(q35;q21) translocations with multiple cases of RCC was reported by investigators in the Netherlands Bodmer et al 1998;Geurts van Kessel et al 1999). Based on the cytogenetic findings, the Netherland translocations appeared to be similar to our familial translocation.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In two living brothers of this family who were diagnosed with renal cell cancers, a t(2;3)(q33;q21) constitutional translocation was found, but it is probable, because of the clinical features of the other five RCC cases that developed in close relatives, that the relatives were also carriers of this chromosomal abnormality. Another family segregating t(2;3)(q35;q21) translocations with multiple cases of RCC was reported by investigators in the Netherlands Bodmer et al 1998;Geurts van Kessel et al 1999). Based on the cytogenetic findings, the Netherland translocations appeared to be similar to our familial translocation.…”
Section: Discussionsupporting
confidence: 78%
“…As yet, only one member of this family developed bilateral renal cell cancer. More recently, a constitutional translocation t(2;3)(q35;q21) was reported in several Dutch family members over three generations, including four patients with renal cell cancers Bodmer et al 1998;Geurts van Kessel et al 1999). Interestingly, at the same time, we identified a family in Poland transmitting a similar constitutional translocation t(2;3)(q33;q21) (Zajaczek et al 1999).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Two living brothers presented with early-onset clear cell renal cancer; kidney cancer was also noted in two earlier generations. A Dutch family with a similar constitutional translocation, t(2,3)(q35;q21), had four family members in three generations with RCCs Bodmer et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The gene was proposed as a tumor suppressor gene and experimental support for the proposal continues to accumulate (Ishii et al 2001;Dumon et al 2001). At the same time, a number of investigators suggested that chromosomal translocations can contribute to kidney cancer initiation or progression, in the sporadic or familial setting, through facilitation of tumor-specific loss of derivative chromosomes carrying large portions of the short arm of chromosome 3 (Gnarra et al 1994;Bodmer et al 1998;Eleveld et al 2001), the locus of several proposed renal cancer tumor suppressor genes, including the VHL gene.…”
Section: Introductionmentioning
confidence: 99%